Diary of wimpy kid the meltdown - Kinney,Jeff (USA: Amulet Books, 2018)
In The Meltdown, the 13th book in the Diary of a Wimpy Kid series, Greg Heffley faces another chaotic year. Set during a snowstorm, the town turns into a winter wonderland, and school is canceled. Greg and his friends find themselves involved in a massive snowball fight that escalates into a full-blown neighborhood war. Greg's best friend, Rowley, gets involved in the action, but their friendship is tested as tensions rise. The war intensifies with both sides constructing snow forts and coming up with strategies to outsmart each other. Throughout the book, Greg's usual antics and his desire to avoid trouble lead to humorous situations and misadventures. As the battle rages on, Greg reflects on his life, family, and friendships, all while trying to stay safe and out of the worst of the chaos. In the end, the snowball fight winds down, and Greg realizes that even though things didn$1 (Bt always go as planned, it was still a memorable experience. The book showcases the usual combination of humor, relatable problems, and Greg's unique perspective on growing up.s
In The Meltdown, the 13th book in the Diary of a Wimpy Kid series, Greg Heffley faces another chaotic year. Set during a snowstorm, the town turns into a winter wonderland, and school is canceled. Greg and his friends find themselves involved in a massive snowball fight that escalates into a full-blown neighborhood war.
Keywords: Friendship; Family